Memperkuat Kesadaran Merek Ramah Lingkungan dan Jangkauan Pemasaran UMKM Bumbu Rempah Ratoeh Indah dengan Pemasaran Digital - Rimadias, Santi; Angin, Pettia Weharima Perangin; Masithah, Siti Nur; Komalasari, Ratna (Journal of Community Service and Society Empowerment, 2024)
Digital marketing plays an important role in strengthening brand awareness and expanding the marketing reach of Micro, Small, and Medium Enterprises (MSMEs). Realizing this important role, the STIE Indonesia Banking School community service team carried out community service activities to support Ratoeh Indah, an MSME, in utilizing digital marketing tools and strategies. The results of initial observations and interviews show that Ratoeh Indah has not utilized the potential of social media for product promotion, nor has she used online shopping platforms or digital advertising to achieve competitive advantage and innovation. Historically, Ratoeh Indah relied on conventional door-to-door sales methods, limiting its reach and growth potential. To address this gap, our intervention includes a comprehensive approach that utilizes SWOT analysis, interviews, observation, and direct mentoring. The main activities include creating and optimizing an Instagram account for product promotion, creating targeted advertisements on Instagram, establishing an online shop on the e-commerce platform Shopee, and implementing more environmentally friendly packaging solutions. The results of the service activities carried out are very significant. There has been a marked increase in brand awareness, evidenced by the growth of Instagram followers and engagement metrics. Additionally, newly established Shopee stores experienced increased visitor traffic, indicating successful penetration into the online shopping realm. The community service undertaken underscores the transformative impact of digital marketing on MSMEs, providing a model for similar companies seeking to strengthen brand awareness and expand marketing reach.